SISTIM PENDUKUNG KEPUTUSAN KLINIS UNTUK MENDUKUNG PEMBUATAN KEPUTUSAN KLINIS PERAWAT : LITERATUR REVIEW - Daniel Dady; Kadek Ayu Erika; Rini Rachmawaty (coba, 2020)
Introduction: Clinical decisions made by nurses must be supported by accurate and complete data and good systems. However, in the implementation of patient care, clinical decision making by nurses is not supported by clinical decision support systems in hospitals.Method: Systematic searches were carried out in several databases namely PubMed, ProQuest, and Science Direct with keywordsSupport SystemClinical Decision AND Clinical Decision Making AND Nurses. Inclusion criteria, namely publications from 2015 to 2019, full text, discuss the use of clinical decision support systems by nurses of all research methods both qualitative, quantitative, mixed methods, cohorts, and surveys and use English.Result: Obtained six research articles according to inclusion criteria. Two studies on developing clinical decision support systems, two studies on evaluating the effect and experience of nurses in using clinical decision support systems, one study on the diagnostic accuracy of clinical decision support systems and one study on barriers to use of clinical decision support systems.Discussion:The clinical decision support system (CDSS) that can be used to support nurses' clinical decisions is NEWS and Tanner's reflection method but must first be tested and socialized regarding the benefits and how to use them to nurses, must be safe for patients and not detrimental to patients and hospitals